IMPLEMENTASI REST API PADA APLIKASI DONOR DARAH BERBASIS MOBILE DAN WEB - Rizky Ramadhani; Adam Sekti Aji (Politeknik Bisnis Indonesia, 2023)
Blood is one of the most important parts of the human body. Blood is useful for circulating oxygen throughout the human body. If someone experiences anemia due to an accident or suffers from anemia, even the accumulation of dirty blood in the body can cause diseases that endanger life, health and even human life. Blood donation activities are the process of transferring blood from donors to people who lack blood and the process is carried out by parties authorized to carry out blood processing processes such as the Blood Transfusion Unit (UTD) under the auspices of the Indonesian Red Cross (PMI). However, PMI's blood stock is sometimes not enough to meet existing blood needs, so patients who need blood must look for donors who have the appropriate blood type. Therefore, a Web and Mobile-based blood donation application with Rest Api was created so that patients can get donors quickly